STUDI TENTANG KEMAMPUAN GURU VOKASI SEKOLAH MENENGAH KEJURUAN NEGERI 2 PAYAKUMBUH DALAM PENGIMPLEMENTASIAN TEKNOLOGI INFORMASI DAN KOMUNIKASI - Okto Ariyosming; Azwar Inra (Teknik Sipil Universitas Negeri Padang, 2021)
This research is motivated by a lot of vocational teachers who cannot implement ICT optimally. This happened allegedly because the majority of vocational teachers were over 40. The purpose of this study was to reveal the ability of vocational teachers at SMKN 2 Payakumbuh in implementing information and communication technology. This type of research is descriptive with a quantitative approach. The population in the study were vocational teachers at SMKN 2 Payakumbuh, totaling 86 people and the research sample amounting to 77 people who were obtained using probability sampling technique, namely simple random sampling. Research data were collected through a questionnaire given to vocational teachers at SMKN 2 Payakumbuh using a Likert scale. Based on the results of the research carried out, it can be concluded that the ability of vocational teachers at SMKN 2 Payakumbuh in implementing ICT is in the medium category, which is 69% or 53 people.